Implementing Agile Scrum Methodology in The Development of SICITRA Mobile Application - Oktavia Citra Resmi Rachmawati; Deyana Kusuma Wardani; Wifda Muna Fatihia; Arna Fariza; Hestiasari Rante (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
Software development management system is important in application development. A proper software development management system will create a team that can adapt to system requirements and changes during application development. Various software development management systems are developed and widely implemented in software development, one of which is Agile Scrum. This study aims to implement well-documented Scrum for end-to-end application development, including the development of servers and mobile applications that we develop. We developed a bus application called SICITRA, with the main feature of being able to help passengers share their travel information with those closest to them. Scrum is used because it has agility which can make application development faster and more organized, and there is a close relationship between everyone involved in the project. The results of this study are that by using well-documented Scrum, we can make it easier to track progress, become a guide during system development, become history and evaluate Scrum implementation during development.